Smart chicken feeder using node MCU ESP8266 / Ilham Syahmin Nasruddin and Mohd Nizam Osman - Nasruddin, Ilham Syahmin; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
This project developed a Smart Chicken Feeder that can be control remotely using smartphone. Signal from smartphone which is sent using Blynk app is received by node MCU through WiFi connection since it designed with Wi-Fi chip. This system is developed to overcome several problems that have been faced by village farmers such as forgot to feed their chicken, irregular feeding schedule and so on. Those problems may affect chicken quality if it’s been left without any action. The project’s product has been tested by several users and a survey have been conducted to gain feedback from respondents on the acceptance of the system. In conclusion, this project developed an affordable feeding system that can be useful to farmers and other users.